2023
DOI: 10.1039/d2gc03989c
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-promoted synthesis of gem-dihaloenones

Abstract: Visible light-promoted strategies were developed for the synthesis of gem-dihaloenones using alkynes and polyhalomethanes as the starting materials. The methods produce a broad range of gem-dibromoenones and gem-dichloroenones without using...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Combined with these experimental outcomes and previous related works [ 17 , 18 , 19 , 20 ], we proposed a plausible mechanism about this photoredox-catalyzed multicomponent annulation of 1,7-diynes. As shown in Scheme 5 , the photocatalytic cycle was initiated by the activation of Ir(III) with blue light irradiation to form the excited state Ir(III)* species, which reacts with BrCCl 3 to yield trichloromethyl radical A and a bromine anion, together with Ir(IV) complex via a single electron transfer (SET).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Combined with these experimental outcomes and previous related works [ 17 , 18 , 19 , 20 ], we proposed a plausible mechanism about this photoredox-catalyzed multicomponent annulation of 1,7-diynes. As shown in Scheme 5 , the photocatalytic cycle was initiated by the activation of Ir(III) with blue light irradiation to form the excited state Ir(III)* species, which reacts with BrCCl 3 to yield trichloromethyl radical A and a bromine anion, together with Ir(IV) complex via a single electron transfer (SET).…”
Section: Resultssupporting
confidence: 77%
“…When a 4 Å molecular sieve was employed as dehydrating agent and dry EtOH as solvent under standard conditions, the reaction process was completely inhibited (Scheme 4b). In addition, the reaction was carried out in the presence of H 2 18 O (98 atom% 18 O), and the products 2a and 2a-O 18 were identified by HR-MS in a 3:1 ratio (Scheme 4c). These two survey results indicated that the oxygen source of the ester and carbonyl group in target products come from water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…130 A similar approach was also proposed by using aqueous DMSO or neat alcohols as reaction media. 131 The generation of a trihalomethyl radical was also exploited in the iron(0) catalysed benzannulation of allylarenes to form 1-halonaphthalenes. 132 Umemoto's reagent 24.1 (Scheme 24) has traditionally been employed in photoredox catalysed trifluoromethylation.…”
Section: Reactions Via Carbon-based Radicalsmentioning
confidence: 99%